Overcoming the Blood–Brain Barrier: Multifunctional Nanomaterial‐Based Strategies for Targeted Drug Delivery in Neurological Disorders - Callan D. McLoughlin; Sarah Nevins; Joshua B. Stein; Mehrdad Khakbiz; Ki‐Bum Lee (Small Science)
The development of effective therapies for neurological disorders is a growing area of research due to the increasing prevalence of these conditions. Some neurological disorders that are prevalent and remain difficult to treat are glioma, neurodegenerative disease, ischemic stroke, and traumatic brain injury. Subsequently, the therapeutic efficacy of small molecules, proteins, and oligonucleotides remains a challenge due to the presence of the blood–brain barrier (BBB), a highly selective semipermeable membrane. To this end, multifunctional nanomaterials have emerged as promising vehicles for targeted drug delivery to the brain, due to their ability to transport therapeutics across the BBB selectively. The design of advanced nanomaterial‐based drug delivery systems capable of overcoming the BBB is influenced by many factors, such as fabrication technique and surface modification. This review explores the diverse range of nanomaterials, including polymer, lipid, gold, magnetic, and carbon‐based nanostructures, capable of effectively passing the BBB. These materials cross the BBB via a variety of established transport mechanisms for targeted delivery of therapeutics to the brain. Moreover, the structure and function of the BBB are highlighted and the potential for nanotechnology to aid the treatment of neurological disorders based on their ability to undergo transcytosis into the brain is highlighted.